Entrepreneurship in emerging economies - Foo, Maw‐Der; Vissa, Balagopal; Wu, Brian (Strategic Entrepreneurship Journal, 2020)
Abstract Research Summary The economic center of gravity is shifting from mature markets to emerging regions. This shift provides a good opportunity to broaden and deepen our theoretical base of concepts and frameworks because emerging and mature regions differ significantly in their institutional regimes. Hence entrepreneurial resource mobilization in emerging regions could differ significantly because of theoretical differences in actors' action logics and resource governance. The eight papers in this special issue provide new empirical evidence on antecedents and consequences of entrepreneurial resource mobilization efforts in emerging regions. Here, we briefly summarize the state of the field, introduce the articles by situating them in a novel theoretical framework on entrepreneurial resource mobilization, and finally using our framework, we suggest opportunities for future research on entrepreneurship in emerging regions. Managerial Summary Entrepreneurship research has advanced mainly using empirical data from the developed economies of North America and Western Europe. Because emerging economies differ markedly in their institutional development from developed economies, this prior research is less likely to be useful to understand entrepreneurship in emerging regions ‐ which are increasingly crucial components of the global economy. This special issue contains eight articles addressing different aspects of the entrepreneurial resource mobilization process using diverse research methods on empirical data drawn from a broad range of emerging economies. This introduction describes the state of the field prior to the special issue, introduces the special issue articles and identifies topics that still need further investigation. We distill the current state of knowledge and offer a roadmap for future scholarship.